2022
DOI: 10.2147/idr.s378574
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenemase- and Colistin Resistant Escherichia coli Strains from Children in China: High Genetic Diversity and First Report of blaNDM-5, blaCTX-M-65, blaOXA-10, blaTEM-1, and mcr-1.1 Genes Co-Occurrence in E. coli ST156

Abstract: Background The emergence of carbapenem and colistin co-resistant Escherichia coli poses a huge challenge to infection control. The purpose of this study was to clarify the mechanism of the carbapenems and colistin co-resistance in E. coli strains. Methods Antimicrobial susceptibility test was carried out by agar dilution methods and colistin resistance was confirmed by broth microdilution methods. Whole genome sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Curiously, STs differed from continent to continent, and as frequent carriers for mcr -1 and bla NDM ( Lin et al, 2020 ; Zhang X. et al, 2022 ), more ARGs and VFs were observed within the ST156 strain prevailing in Asia and Europe, indicating that it represents a major risk to public health, highlighting the need for increased surveillance. For example, E. coli ST156, carrying bla NDM–5 , bla CTX–M–65 , bla OXA–10 , bla TEM–1 , and mcr -1, has been found in clinical isolates in China ( Lin et al, 2020 ; Zhang X. et al, 2022 ). Notably, ST648 has been reported as a high-risk, MDR, ESBL-producing strain in public aquatic environments ( Furlan et al, 2020 ), but ST648 was not frequently detected in our study, with almost all of them being in North America.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, STs differed from continent to continent, and as frequent carriers for mcr -1 and bla NDM ( Lin et al, 2020 ; Zhang X. et al, 2022 ), more ARGs and VFs were observed within the ST156 strain prevailing in Asia and Europe, indicating that it represents a major risk to public health, highlighting the need for increased surveillance. For example, E. coli ST156, carrying bla NDM–5 , bla CTX–M–65 , bla OXA–10 , bla TEM–1 , and mcr -1, has been found in clinical isolates in China ( Lin et al, 2020 ; Zhang X. et al, 2022 ). Notably, ST648 has been reported as a high-risk, MDR, ESBL-producing strain in public aquatic environments ( Furlan et al, 2020 ), but ST648 was not frequently detected in our study, with almost all of them being in North America.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the co-carriage of multiple RTs among a single E. coli strain has been frequently reported. For instance, a single E. coli strain from children in China co-carried with bla NDM−5 , bla CTX−M−65 , and mcr-1.1 [12], while E. coli strains from northeast India acquired 16S rRNA methyltransferases (16S-RMTase) along with bla CTX−M−15 , bla NDM , and bla OXA−48 [13]. Whole-genome sequencing (WGS) is a useful tool for studying the molecular epidemiology of pathogens from human, animal, and environmental sources.…”
Section: Introductionmentioning
confidence: 99%
“…Co-transmission of CTX-M-65 with other ESBL-ARGs in E. coli have also been reported more frequently, ultimately leading to an increased risk of livestock-to-human transmission and global multidrug resistance (MDR) through horizontal gene transfer (HGT) [ 11 14 ]. Note that bla CTX-M-65 gene, with an elevated detection rate, has been reported in food animals [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%